2001
DOI: 10.1530/eje.0.1450791
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of 20 kDa and 22 kDa human growth hormones on adult male spontaneous dwarf rats

Abstract: Background: Two molecular forms of human GH (hGH) have been shown to be biologically active. The 20 kDa form has been reported to have weaker diabetogenic and lipolytic actions than the 22 kDa form. Objective: To analyze the carbohydrate metabolism of 20 kDa and 22 kDa hGH, using the adult male spontaneous dwarf rat (SDR), which is GH deficient. Design: SDRs were given 20 kDa or 22 kDa hGH in doses of 125 mg/rat or 500 mg/rat, or saline, for 10 days, and their weight, serum IGF-I, glucose, insulin, leptin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Body weights and serum IGF-I increased dosedependently in both 20K-GH and 22K-GH treated groups [6]. Study on the osteo-anabolic effect of GH in cultured human osteoblastlike cells revealed that both 20K-GH and 22K-GH stimulated bone remodeling and exhibit equipotent anabolic effects on skeletal tissues [7].…”
Section: Biological Effectmentioning
confidence: 99%
“…Body weights and serum IGF-I increased dosedependently in both 20K-GH and 22K-GH treated groups [6]. Study on the osteo-anabolic effect of GH in cultured human osteoblastlike cells revealed that both 20K-GH and 22K-GH stimulated bone remodeling and exhibit equipotent anabolic effects on skeletal tissues [7].…”
Section: Biological Effectmentioning
confidence: 99%
“…This isoform is generated by alternative splicing within exon 3 of the GH primary transcript, resulting in the deletion of residues 32-46 of 22-kDa GH (1,6). The 20-kDa GH has growthpromoting and lipolytic activities similar to those of 22-kDa GH (18,25) but has reduced antinatriuretic activity (21). Although these observations suggest that it has a slightly different metabolic profile, the physiological role of 20-kDa GH is not known.…”
mentioning
confidence: 99%
“…Subsequent studies have yielded conflicting information in this regard, perhaps in part due to species differences [29][30][31]. The growth promoting activity of 20K-GH in vivo has been found to be similar to that of 22K-GH in the rat [10,[32][33][34] despite diminished affinity of 20K-GH for the GHR (see below). In the obese mouse 20K-GH had mildly diminished growth-promoting and lipolytic activity compared to 22K-GH [35], but the two GH isoforms had equipotent lipolytic activity in chicken adipose tissue [36].…”
Section: K-ghmentioning
confidence: 99%